An investigation on stressing and breakage response of a prestressing strand using an efficient finite element model. (15th September 2016) - Abdullah, A.B.M.; Rice, Jennifer A.; Hamilton, H.R.; Consolazio, Gary R.
Highlights: Wire breakage is simulated to characterize the post-breakage behavior of a prestressing strand. The effects of modeling parameters on strand response are investigated. Breakage in an outer wire results in greater prestress loss than that in the center wire. The onset of interwire motion redistributes the load sharing among the wires. The natural frequency of strand shifts with successive wire breaks. Abstract: The mechanical response of a wire strand is inherently complex because the helical wires undergo evolving stress and contact conditions as the strand is loaded. Further complications are added to the strand behavior if one or more of the wires break due to strand degradation over time. Although a detailed investigation on strand behavior is critically important for predicting the capacity of a broken strand as well as developing new monitoring approaches for wire break detection, there is little study available in the literature on wire breakage in a stressed strand. This paper provides an extensive investigation on stressing and post-breakage dynamic behavior of a prestressing strand. A finite element model is generally useful to study the global strand response, along with many localized phenomena that have strong influence on its performance, but are difficult to capture either experimentally or through closed-form analytical models. Investigations on certain behaviors, such as wire breaks, however, require a relatively large or even a full-scale model to adequately develop contact and frictional conditions. Moreover, such a sizeable model can account for any deviation points and may avoid edge effects. Consequently, several finite element parameters, such as the load ramp profile and duration, effects of damping and interwire friction, become critical for an accurate and efficient model. This paper first presents the use of a parametrized model to study strand behavior and evaluates the effects of these modeling parameters on strand response; load distribution and redistribution among the wires at the onset of interwire motion are also considered. The model is then used to simulate wire breakage in a prestressing strand, so that various aspects of post-breakage response can be examined. Numerical results show that a linear load ramp or stressing too quickly may lead to an inaccurate axial tension developed in the strand, whereas the inclusion of nominal mass-based damping has been found effective in achieving a quasi-static solution at a reasonable computational cost. In addition, the wire break simulation results indicate that breakage of an outer wire results in greater prestress loss than breakage of the center wire, which might have important implications for non-destructive wire breakage detection.